Triumph and tragedy in Travancore : annals of Sir CP's sixteen years - Sreedhara Menon, A. (Current Books, 2001)
Role and contribution of Sir Chetpat Pattabhirama Ramaswami Aiyar, 1879-1966, Diwan and legal advisor to ruler of Travancore State, in the making of modern Travancore during 1931-1947.